Power to the People: Black Publishing for Social Change in South Africa - le Roux, Elizabeth (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
The black power salute is a powerful call to arms for resistance and social change. In South Africa, black power is tied up with the Black Consciousness Movement of the 1970s, aiming to reclaim black identity. Integral to this attempt was the use of cultural and intellectual means, and under its aegis writers’ groups started forming in place of political groups (which were suppressed), as a base for mobilisation and collective action. But these writers could not effect social change on their own: they needed a platform—a publisher. Sipho Sepamla, writing in the New Classic in 1976, pointed to the absence of publishers as a hurdle for black writers: ‘A problem that wears us down is lack of publishers and outlets. There is not a single black publisher I know of in this country.’ In the context of the competing forces of repression and Black Consciousness, a few black publishers did emerge. Skotaville Press, for instance, aimed ‘to produce black literature that is relevant and contemporary—and to do it under black control from start to finish.’ However, it did this in somewhat ambiguous circumstances, relying on foreign funds and white patrons. Using archival records and interviews, this paper will assess the operations and output of these publishers, considering how race and context affects and inflects publishing. Moreover, it will ask why, in contrast to the legacy created by black power publishers in the US, a tradition of viable black‑owned publishing has not continued into the post‑apartheid period.